Comparative Study on Bending Strength of Metallic Bone Staple - Hidayatul Nadhirah Elmi Azham Shah, Nur; Afiq Hanizar, Muhammad; Hussain Ismail, Muhammad (International Journal of Engineering and Technology, 2018)
This study compares bending behavior of metallic bone staples made with different metallic alloys; SS316L, CpTi and Ti40Nb. The staples were prepared by EDM wire cut in accordance with ASTM F564-10, standard specification and test methods for metallic bone staples. The materials of SS316L and CpTi were initially obtained from commercial rod, while the Ti40Nb alloy was manufactured by powder metallurgy (PM) process. Through this comparative study, development and feasibility of Ti40Nb, a Î²-rich TiNb alloy performance as a biomedical device specifically bone staple is studied. In the four point bending test, the data obtained for the metallic staple bending strength were 11.16Â±1.57 N/mm, 12.22Â±1.77 N/mm and 6.76Â±0.46 N/mm for SS316, CpTi and Ti40Nb, respectively. Only Ti40Nb experience failure whereas SS316 and CpTi bone staples suffers permanent deformation without failure.Â Â